Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

From the sum of 3x – y + 11 and – y – 11, subtract 3x – y – 11.

 From the sum of 3x – y + 11 and – y – 11, subtract 3x – y – 11.

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5859 Points
3 months ago
Dear Student

First we have to find out the sum of 3x–y + 11 and–y–11
= 3x–y + 11 + (-y - 11)
= 3x–y + 11–y–11
= 3x–y–y + 11–11
= 3x–2y
Now, subtract 3x–y–11 from 3x–2y
= 3x–2y–(3x–y - 11)
= 3x–2y–3x + y + 11
= 3x–3x–2y + y + 11
= -y + 11

​Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free